Tunable Photo‐Electrochemistry of Patterned TiO2/BDD Heterojunctions. Issue 9 (15th June 2020) - Jian, Ze; Yang, Nianjun; Vogel, Michael; Zhou, Zhaoyu; Zhao, Guohua; Kienitz, Paul; Schulte, Anna; Schönherr, Holger; Jiao, Tianpeng; Zhang, Wenjun; Jiang, Xin
Abstract: Heterojunctions are especially attractive for photo‐electrocatalytic applications if both high‐performance photo and electrocatalysts are employed for their construction. Herein, a p–n heterojunction is synthesized using uniform patterns of p‐type boron doped diamond (BDD) and an n‐type anatase TiO2 film. The exposure ratios of the BDD patterns are varied to tune the photo‐electrocatalytic abilities of this heterojunction. A heterojunction with a BDD exposure ratio of 20% exhibits a photocurrent density of 0.63 mA cm −2, which is 2.86‐fold higher than that obtained on a BDD film and 1.91‐fold higher than that obtained on a TiO2 film coated on a BDD film. It completely degrades methyl orange within 4 h, following the application of a 2.5 V bias potential, while the degradation efficiency on the BDD film and the TiO2 film is 56% and 45%, respectively. As confirmed by electron spin resonance spectroscopy, an accelerated production rate of OH radicals is realized on this heterojunction. It originates from a synergistic effect between the BDD patterns that act as an ultra‐microelectrode array with a TiO2 /BDD p–n heterojunction as well as facilitated charge separation in a lateral direction. This TiO2 /BDD patterned heterojunction is thus promising as a new photo‐electrocatalyst for various catalytic applications. Abstract : Patterned heterojunctions formed from p‐type boron‐doped‐diamond rectangles and an n‐type anatase TiO2 film feature high but tunable photo‐electrocatalytic activity toward photo‐electrochemical degradation of environmental pollutants. It originates from a synergistic effect between a boron‐doped‐diamond ultra‐microelectrode array, a TiO2 /BDD p–n junction and the facilitated charge separation in a lateral direction, leading to the accelerated generation of OH radicals.